1997
DOI: 10.1164/ajrccm.155.6.9196116
|View full text |Cite
|
Sign up to set email alerts
|

Cellular association of antiproteases in lavages from ventilated preterm human neonates.

Abstract: Lung antiprotease activity is routinely assayed in the supernatant of bronchoalveolar lavage fluid (BALF). In this study the cellular fraction of lavages was also analyzed. Functionally active acid-resistant inhibitors with molecular masses characteristic of the mucus proteinase inhibitor (MPI, 14 kDa) and elastase-specific inhibitor (ESI, 7 kDa) were demonstrated by gel chromatography. Immunocytochemical studies of cells obtained at various postnatal time points from lavages of 10 premature infants with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…A substantial fraction of the acid-resistant inhibitors is associated with the cellular fraction of lavage samples, as previously shown (6). Elastase-specific inhibitor was expressed by these cells, whereas MPI was merely bound to neutrophils or macrophages, without expression of a significant amount of mRNA.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…A substantial fraction of the acid-resistant inhibitors is associated with the cellular fraction of lavage samples, as previously shown (6). Elastase-specific inhibitor was expressed by these cells, whereas MPI was merely bound to neutrophils or macrophages, without expression of a significant amount of mRNA.…”
supporting
confidence: 69%
“…Besides synthesis by mucosal cells in the airways (5), our previous study in a comparable group of preterm neonates suggested the synthesis of ESI, but not of MPI, and the association of MPI with a substantial fraction of the neutrophils and macrophages of the cellular lavage fraction (6). We did not find expression of MPI in pilot experiments on unstimulated human neutrophils from peripheral blood or macrophages from healthy adult volunteers (6). Recently, it was demonstrated that neutrophils and peritoneal macrophages from mice synthesize MPI (or SLPI) after lipopolysaccharide (LPS) stimulation (15).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The enzymatic activity of the human leukocyte elastase (HLE) was determined spectrophotometrically with the specific substrate N-Suc-Ala-Ala-Ala-p-nitroanilide (Elastin Products, Owensville, MO, USA), similarly as described previously [21]. All samples were assessed in triplicate.…”
Section: Determination Of Human Leukocyte Elastase Activitymentioning
confidence: 99%